THE INFLUENCE OF USING THE GIST STRATEGY IN TEACHING RECOUNT TEXT - Ramlah, Salma; Talib, Ahmad; G, Hasriani (Universitas Negeri Makassar, 2024)
This study aims to investigate the effects of teaching recount text using the GIST (Generating Interaction between Schemata and Text) technique. Meanwhile, the purpose of this study is to determine whether or not students' comprehension of recount texts has increased. This study was conducted during the second semester of SMPN 4 Sungguminasa's ninth grade. With a pretest and posttest for a single group, the researcher employed a pre-experimental design. The sample consisted of 34 pupils from class 9K, whereas the population consisted of all ninth-grade students. Using SPSS 26, the researcher analyzed the data. As a consequence, the posttest's mean score of 49.26 exceeds the pretest's mean score of 77.21. Additionally, the probability value (sig.2-tailed: 0.000) is lower, according to the paired sample t-test. Also, the paired sample t-test shows that the probability value (sig.2-tailed: 0.000) is lower than (< 0.05). It means, there were significant differences in the average in using GIST strategy in teaching recount text. In conclusion, the alternative hypothesis (H1) in this study is accepted, and the null hypothesis (H0) is rejected. In addition, GIST strategy increases students’ comprehension of recount text.